Organizational Citizenship Behavior Based on Spirituality and Employee Performance: The Role of Communication and Engagement - Thamrin, Mohammad; Samsuryaningrum, Ira Puspitadewi; Hassan, Zainudin (Universitas Brawijaya, Indonesia, 2024)
Institutions that provide zakat amil have lofty social objectives. Enhancing employee performance within these institutions has the potential to improve community services and have a larger social impact. Spiritual principles frequently serve as the foundation for work ethics and motivation in zakat amil institutions. The study aims to examine how employee engagement and interpersonal communication are mediated by organizational citizenship behavior based on spirituality (OCBBOS) and how this affects the work output of employees at Amil Zakat Institution. The Amil Zakat Institutions located in the province of East Java include the population under study. The sampling method used is proportional random sampling. Structural Equation Modeling (SEM) using SmartPLS is the data analysis technique employed in this study. The study's findings indicate that OCBBOS is influenced by interpersonal interactions and employee engagement. Employee performance is influenced by interpersonal communication and employee engagement. Employee performance is impacted by OCBBOS. Through OCBBOS, interpersonal communication and employee engagement affect employee performance. The novelty of the research is that OCBBOS is an intervening variable because OCBBOS is an organizational behavior factor that can influence a person's performance. The research's practical implication is that it can serve as a model for other social institutions looking to better achieve social goals by fusing administrative techniques and spiritual principles.